Analisis Peran Media Sosial Dalam Meningkatkan Branding Wisata Jolotundo Glamping And Edu Park Nganjuk - Ibnu Tholibin; Mas’ut; Sony Eko Adisaputro (Bahasa Indonesia, 2024)
This research aims to analyze the role of social media in enhancing the branding of Jolotundo Glamping and Edupark Nganjuk. The main challenges in improving tourism branding include competition with other destinations, the growth of global connectivity, information technology, and competition among destinations. These factors require effective marketing strategies. Additionally, changes in consumer trends and technology can affect the effectiveness of social media strategies. Social media has significant power in reaching a broad audience and influencing public perception of a destination. In the context of tourism, social media plays a crucial role in increasing widespread popularity and building a positive image of this destination. The data collection techniques used in this research include observation, interviews, and documentation. Data analysis is conducted using qualitative descriptive methods. The research findings show that social media can enhance the branding of Jolotundo Glamping and Edupark through the planning of forming a special social media team, selecting social media platforms, and engaging third parties. The implementation involves having a dedicated social media team, choosing Instagram, TikTok, and YouTube, and collaborating with third parties such as Niken Salindri and Woko Chanel. The impact of social media includes an increase in the number of tourists, a rise in social media engagement, and an increase in the diversity of visitor origins.